Essentials of terrorism : concepts and controversies - Martin, Gus (Los Angeles : SAGE, 2022)
"Captivating, concise, and accessible, Essentials of Terrorism: Concepts and Controversies covers key foundational topics by defining terrorism and introducing its history and causes. Author Gus Martin introduces readers to the modern landscape of terrorism, discusses terrorist environments (domestic, international, religious, etc.), as well as tactics, targets, and counterterrorism. Included in this 6th edition is an added focus on U.S. hate crimes and homeland security, in addition to new introductory discussions, information, and data throughout each chapter. Key Features: Discussion boxes stimulate critical thinking and encourage classroom discussions and debates about timely topics. End-of-chapter material, including Key Terms and Internet Exercises, help readers fully understand key concepts. Fully updated tables and figures are included to present an empirical summary of discussions and concepts, allowing readers to conduct insightful research and analyses"--
Revised edition of the author's Essentials of terrorism, [2019]
Includes bibliographical references and index.
Keywords: Terrorism